Eléments déterminant l’impact de l’e-GP sur la transparence des procédures des marchés publics à Madagascar - TADAHY Leong Francis; RAZAFINDRAVONONA Jean (Progress in Science, 2024)
Transparency in public procurement via e-GP, as in the case of Madagascar, depends on a number of factors, including the country’s technological maturity. Suitable digital infrastructures are needed to implement and maintain an effective e-GP. As sensitive information is involved, data security is essential. To achieve transparency, stakeholders must have access to the platform, and at the same time be trained in the use of e-GP. The level of education of stakeholders plays a crucial role, as an educated population more easily understands the challenges of transparency and the use of digital tools.